Regulating cellular metabolism and morphology to achieve high-yield synthesis of hyaluronan with controllable molecular weights - Litao Hu; Sen Xiao; Jieyu Sun; Faying Wang; Guobin Yin; Wenjie Xu; Jianhua Cheng; Guocheng Du; Jian Chen; Zhen Kang (Nature Communications)
Abstract High-yield biosynthesis of hyaluronan (HA) with controllable molecular weights (MWs) remains challenging due to the poorly understood function of Class I HA synthase (HAS) and the metabolic imbalance between HA biosynthesis and cellular growth. Here, we systematically characterize HAS to identify crucial regions involved in HA polymerization, secretion, and MW control. We construct HAS mutants that achieve complete HA secretion and expand the MW range from 300 to 1400 kDa. By dynamically regulating UDP-glucose 6-dehydrogenase activity and applying an adaptive evolution approach, we recover cell normal growth with increased metabolic capacities. Final titers and productivities for high MW HA (500 kDa) and low MW HA (10 kDa) reach 45 g L−1 and 105 g L−1, 0.94 g L−1 h−1 and 1.46 g L−1 h−1, respectively. Our findings advance our understanding of HAS function and the interplay between cell metabolism and morphology, and provide a shape-guided engineering strategy to optimize microbial cell factories.